2023
DOI: 10.1111/1365-2435.14283
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of hydraulic and morphological traits across dominant grasses in eastern Australia

Abstract: Leaf hydraulic traits characterize plant drought tolerance and responses to climate change. Yet, plant hydraulics are biased towards northern hemisphere woody species. We collected rhizomes of several perennial grass species along a precipitation gradient in eastern Australia and grew them in an experimental pot study to investigate potential trade‐offs between drought tolerance and plant morphology. We measured the following leaf hydraulic traits: the leaf water potential (Ψleaf) at 50% and 88% loss of leaf h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Niinemets, 2001; Griffith et al ., 2016). Similarly, this result complements patterns of coordination between hydraulic traits and LDMC (Griffith et al ., 2016; Griffin‐Nolan et al ., 2023) that are critical for describing ecosystem drought responses (Blumenthal et al ., 2020; Wilcox et al ., 2021). In our phylogenetically controlled analysis, tall plants with higher LDMC and foliar C : N are associated with lower V c max .…”
Section: Discussionmentioning
confidence: 99%
“…Niinemets, 2001; Griffith et al ., 2016). Similarly, this result complements patterns of coordination between hydraulic traits and LDMC (Griffith et al ., 2016; Griffin‐Nolan et al ., 2023) that are critical for describing ecosystem drought responses (Blumenthal et al ., 2020; Wilcox et al ., 2021). In our phylogenetically controlled analysis, tall plants with higher LDMC and foliar C : N are associated with lower V c max .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the effects of environmental variability have focused on the linkage between climatic changes, plant populations (Wang & Gao, 2003 ; Yuan et al., 2016 ), and morphological traits (Cardou et al., 2022 ; Griffin‐Nolan et al., 2023 ; Hounkpevi et al., 2020 ). Wang and Gao ( 2003 ) found that Leymus chinensis adjusts to decreasing mean annual precipitation (MAP)/increasing aridity by altering shoot density and biomass allocation along large‐scale drought gradients (Wang & Gao, 2003 ).…”
Section: Introductionmentioning
confidence: 99%